Robotic System for Maintenance of Feed Table for Livestock Complexes - D. Yu. Pavkin; E. A. Nikitin; V. A. Zobov (Сельскохозяйственные машины и технологии, 2020)
Assessing the robotization level of technological processes in livestock complexes based on the breeding, authors found that the most free niche of robotization of technological processes in livestock complexes is the feeding process, which forms 55 percent of milk productivity. There is a need to develop a wheeled robotic platform that will ensure the availability of the feed mixture along the feeding front. This platform will multi-stage saturate the bulky components of the feed mixture with concentrated ones, increasing their attractiveness to animals, while normalizing the balance of dry matter consumed and fiber obtained from bulky feeds.(Research purpose) To simulate the control system of a robotic platform with an independent electro- motorized drive.(Materials and methods) The article presents technologies for organizing animal feeding processes on the farm, conducted a technological assessment of the effectiveness of automated and robotic machines used on the farm. Authors used the Matlab/Simulink simulation environment in the research process.(Results and discussion) The article presents a developed mathematical model describing the kinematics and dynamics of the platform movement. Authors formed the assumed element base into a general model of the robot in an artificial Matlab/Simulink environment, simulating the process of moving around a circle.(Conclusions) The created mathematical model forms the basis for creating a control system for the robot under development. The device for dosing feed additives will ensure the balance of dry matter and fiber consumed.